2020
DOI: 10.3390/molecules25225455
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Polyethyleneimine with Hollow Cyclotriveratrylene and Its Subsequent Supramolecular Interaction with Doxorubicin

Abstract: In this paper, a modified Cyclotriveratrylene was synthesized and linked to a branched Polyethylenimine, and this unique polymeric material was subsequently examined as a potential supramolecular carrier for Doxorubicin. Spectroscopic analysis in different solvents had shown that Doxorubicin was coordinated within the hollow-shaped unit of the armed Cyclotriveratrylene, and the nature of the host–guest complex revealed intrinsic Van der Waals interactions and hydrogen bonding between the host and guest. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 81 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…The cross-linked polymer Cross-PEI-800 was prepared as shown in Scheme 1 . Precursor 2a was obtained by reacting vanillyl alcohol with 1,4-dibromobutane, as reported in the literature [ 18 , 66 , 67 , 68 ]. The oligomerization of compound 2a with scandium triflate in CH 3 CN afforded Armed-CTV [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cross-linked polymer Cross-PEI-800 was prepared as shown in Scheme 1 . Precursor 2a was obtained by reacting vanillyl alcohol with 1,4-dibromobutane, as reported in the literature [ 18 , 66 , 67 , 68 ]. The oligomerization of compound 2a with scandium triflate in CH 3 CN afforded Armed-CTV [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Precursor 2a was obtained by reacting vanillyl alcohol with 1,4-dibromobutane, as reported in the literature [ 18 , 66 , 67 , 68 ]. The oligomerization of compound 2a with scandium triflate in CH 3 CN afforded Armed-CTV [ 18 ]. The PEI-800 was cross-linked with Armed-CTV in DMSO overnight to obtain the highly water-soluble product Cross-PEI-800 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DOX-HPR peaks detected by UV and RI appeared at similar retention times, suggesting that DOX molecules were chemically conjugated with HPR. In the 1 H NMR spectrum of DOX-HPR, peaks assignable to the anthraquinone ring of DOX appeared at 7.63, 7.71, and 7.97 ppm ( Figure 3 B) [ 37 ]. In accordance with these results, we concluded that DOX-HPR was successfully prepared without contamination with free DOX.…”
Section: Resultsmentioning
confidence: 99%